Peran Guru Pendidikan Agama Islam dalam Membina Akhlakul Karimah untuk Meningkatkan Kemandirian Peserta Didik SMA-IT Miftahul Khoir Dago Bandung - Amelia; Sobar Al Ghazal; Helmi Aziz (Bandung Conference Series: Islamic Education, 2022)
Abstract. There were students who still did not practice good morals, while at SMA-IT Miftahul Khoir there was already moral development. So from that moment on, fostering moral character for the independence of students needs to be improved again so that students who have good morals are created and are able to become independent students. Fostering moral character to increase the independence of students in order to achieve it, it is necessary to know and understand the factors that influence moral development to increase independence so that the expected learning objectives can be achieved. Based on these conditions, the researcher is interested in researching "The Role of Islamic Religious Education Teachers in Fostering Akhlakul Karimah to Increase the Independence of SMA-IT Miftahul Khoir Students." The results of the coaching of students starting with poor morals starting from forgiveness, trustworthiness, morals, and being able to do well in accordance with Islamic teachings. The results of the existence of which increase independence are being able to take responsibility for themselves and others by being able to solve the problems that befell them. The purpose of this study was to determine, describe, and analyze the factors that influence the role of Islamic religious teachers in fostering morality and morality to increase the independence of students towards Islamic Religious Education subjects at SMA-IT Miftahul Khoir. The method used in this research is a descriptive method with a qualitative approach and the type of research is case research. The data collection techniques used are observation, interviews, and documentation. The population and sample of this study were school principals, religious teachers, and students of class XI SMA-IT Miftahul Khoir Bandung. The results of this study are the factors that influence in fostering the morals of class XI students on the subjects of Islamic Religious Education at SMA-IT Miftahul Khoir, namely by fostering morals of class XI students. Abstrak. Masih ada siswa yang belum mengamalkan akhlak yang baik, sedangkan di SMA-IT Miftahul Khoir sudah ada pembinaan akhlak. Maka mulai saat itu pembinaan akhlak untuk kemandirian siswa perlu ditingkatkan lagi agar tercipta siswa yang berakhlak baik dan mampu menjadi siswa yang mandiri. Pembinaan akhlakul karimah untuk meningkatkan kemandirian peserta didik agar dapat mencapainya, perlu diketahui dan dipahami faktor-faktor yang mempengaruhi perkembangan akhlak untuk meningkatkan kemandirian sehingga tujuan pembelajaran yang diharapkan dapat tercapai. Berdasarkan kondisi tersebut, peneliti tertarik untuk meneliti “Peranan Guru Pendidikan Agama Islam dalam Menumbuhkan Akhlakul Karimah Untuk Meningkatkan Kemandirian Siswa SMA-IT Miftahul Khoir”. Hasil pembinaan peserta didik dimulai dari akhlak yang buruk mulai dari pemaafan, amanah, akhlak, dan mampu berbuat baik sesuai dengan ajaran Islam. Hasil dari eksistensi yang meningkatkan kemandirian adalah mampu bertanggung jawab terhadap diri sendiri dan orang lain dengan mampu memecahkan masalah yang menimpa dirinya. Tujuan penelitian ini adalah untuk mengetahui, mendeskripsikan, dan menganalisis faktor-faktor yang mempengaruhi peran guru agama Islam dalam membina akhlak dan akhlak untuk meningkatkan kemandirian siswa terhadap mata pelajaran Pendidikan Agama Islam di SMA-IT Miftahul Khoir. Metode yang digunakan dalam penelitian ini adalah metode deskriptif dengan pendekatan kualitatif dan jenis penelitiannya adalah penelitian kasus. Teknik pengumpulan data yang digunakan adalah observasi, wawancara, dan dokumentasi. Populasi dan sampel penelitian ini adalah kepala sekolah, guru agama, dan siswa kelas XI SMA-IT Miftahul Khoir Bandung. Hasil penelitian ini adalah faktor-faktor yang berpengaruh dalam pembinaan akhlak siswa kelas XI pada mata pelajaran Pendidikan Agama Islam di SMA-IT Miftahul Khoir yaitu dengan pembinaan akhlak siswa kelas XI.